2019
DOI: 10.1016/j.engstruct.2019.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Variable friction cladding connection for seismic mitigation

Abstract: Cladding systems are conventionally designed to serve an architectural purpose and provide environmental protection for building occupants. Recent research has been conducted to enhance structural resiliency by leveraging cladding systems against man-made and natural hazards. The vast majority of the work includes the use of sacrificial cladding panels and energy dissipating connectors. These passive protection systems, though effective, have typically targeted a single hazard one-at-a-time because of their li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…Seismic loads are simulated using the set of six earthquake events used in [39]. The ground motion records are extracted from the PEER ground motion database.…”
Section: External Loadsmentioning
confidence: 99%
“…Seismic loads are simulated using the set of six earthquake events used in [39]. The ground motion records are extracted from the PEER ground motion database.…”
Section: External Loadsmentioning
confidence: 99%
“…On the other hand, concerning MF systems, it is desirable to endow the connection with enhanced dissipative features. Various types of devices can be conceived for this purpose and the use of high-damping or smart materials, like, for example, friction-based or Shape Memory Alloys might contribute to improve the performances of the MF systems [12,15,17].…”
Section: Effect Of Damping Of the Connectionsmentioning
confidence: 99%
“…The idea to exploit cladding displacements to improve building performances with respect to blasts and extreme seismic excitations goes back at least to [13] and led several authors to evaluate the possibility to design moving connections with relevant energy-dissipation capabilities (see, e.g., [14,15] among many others).…”
Section: Introductionmentioning
confidence: 99%
“…wind (Gong et al, 2019a), seismic (Gong et al, 2019b), and blast (Cao et al, 2018b). The objective of this paper is to integrate these results for multi-hazard mitigation by meeting multi-objective requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the VFCC’s friction mechanism has been conducted in a laboratory environment on a prototype (Gong et al, 2018). The authors have also developed MBD procedures and numerically demonstrated the ability of the VFCC to improve building performance under three individual hazards: wind (Gong et al, 2019a), seismic (Gong et al, 2019b), and blast (Cao et al, 2018b). The objective of this paper is to integrate these results for multihazard mitigation by meeting multiobjective requirements.…”
Section: Introductionmentioning
confidence: 99%